UPAYA PENINGATAN PENGUASAAN VOCABULARY BAHASA INGGRIS DENGAN MENGGUNAKAN MODEL TEAM GAMES TOURNAMENT PADA SISWA KELAS V SD NEGERI 4 KARANGDUWUR TAHUN AJARAN 2013/2014 - TRIANTO, JUNI (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The effort to improve The Mastery English Vocabulary using Teams Games Tournament models in fifth grade of SDN 4 Karangduwur. The purpose of this research is describe the use of Teams Games Tournament models that can improving the mastery of Students English vocabulary. This research utilize Classroom Action Research. Action performing is performed in three cycles. The subjects were elementary school students in fifth grade with 20 students. Data collection techniques using test, observation, questionnaire, documentation and interview. The result show the using of Teams Games Tournament models can improving mastery of students English vocabulary. Keywords: TGT, vocabulary, English